Legal Implications of the Application of Restorative Justice to Narcotics Crimes in Order to Realize Restorative Justice and Rehabilitation for Perpetrators - Hia, Renovasi; Setiono, Joko; Koto, Zulkarnein (Greenation Publisher & Yayasan Global Resarch National, 2025)
Narcotics crime is one form of offense that has systemic impacts on public health, security, and order. The conventional penal system, which tends to focus on imprisonment, has not been entirely effective in addressing the root problems of narcotics abuse, especially among users. As an alternative in this situation, the restorative justice method seeks to rebuild the community, the victim, and the criminal via communication and rehabilitation. In order to achieve restorative justice and offenders' rehabilitation, this study looks at the legal ramifications of applying restorative justice to drug-related offenses. Law Number 35 of 2009 about narcotics, Supreme Court Regulation Number 4 of 2010, Attorney General Regulation Number 15 of 2020, and Law Number 1 of 2023 about the Criminal Code are all reviewed using a normative method. The study's findings demonstrate that restorative justice is only appropriate for drug users who meet specific requirements, such as not being a recidivist and having a limited amount of evidence. The application of this approach has a positive impact on reducing overcrowding in correctional institutions and fulfilling the offender’s human rights to receive rehabilitation. However, there are still obstacles such as the lack of explicit regulations in the Narcotics Law and the limited availability of adequate rehabilitation facilities. Policy reformulation and the strengthening of synergy among law enforcement officers are important steps in expanding the comprehensive implementation of restorative justice in the future.